Three-dimensional kinematic and kinetic gait deviations in individuals with chronic anterior cruciate ligament deficient knee: A systematic review and meta-analysis. (June 2016) - Ismail, Shiek Abdullah; Button, Kate; Simic, Milena; Van Deursen, Robert; Pappas, Evangelos
Abstract: Background: Altered joint motion that occurs in people with an anterior cruciate ligament deficient knee is proposed to play a role in the initiation of knee osteoarthritis, however, the exact mechanism is poorly understood. Although several studies have investigated gait deviations in individuals with chronic anterior cruciate ligament deficient knee in the frontal and transverse planes, no systematic review has summarized the kinematic and kinetic deviations in these two planes. Methods: We searched five electronic databases from inception to 14th October 2013, with key words related to anterior cruciate ligament, biomechanics and gait, and limited to human studies only. Two independent reviewers assessed eligibility based on predetermined inclusion/exclusion criteria and methodological quality was evaluated using the Strengthening the Reporting of Observational Studies in Epidemiology statement checklist. Findings: We identified 16 studies, totaling 183 subjects with anterior cruciate ligament deficient knee and 211 healthy subjects. Due to the variability in reported outcomes, we could only perform meta-analysis for 13 sagittal plane outcomes. The only significant finding from our meta-analysis showed that individuals with anterior cruciate ligament deficient knee demonstrated a significantly greater external hip flexor angular impulse compared to control (P = 0.03). Interpretation: No consensus about what constitutes a typical walking pattern in individuals with anterior cruciate ligament deficient knee can be made, nor can conclusions be derived to explain if gait deviations in the frontal and transverse plane contributed to the development of the knee osteoarthritis among this population. Highlights: Limited evidence of gait deviations in chronic anterior cruciate deficient knee Chronic anterior cruciate deficient knee showed greater hip flexor angular impulse Unable to attribute gait deviations to development of knee osteoarthritis